Dark Soliton Solutions of Klein-Gordon-Zakharov Equation in (1+2) Dimensions - Demiray, Seyma Tuluce; Bulut, Hasan (Amer Inst Physics, 2017)
This study base on dark soliton solutions of Klein-Gordon-Zakharov (KGZ) equation in (1+2) dimensions. The generalized Kudryashov method (GKM) which is one of the analytical methods has been handled for finding exact solutions of KGZ equation in (1+2) dimensions. By using this method, dark soliton solutions of this equation have been obtained. Also, by using Mathematica Release 9, some graphical simulations were done to see the behavior of these solutions.
11th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 04-08, 2016 -- Univ La Rochelle, La Rochelle, FRANCE